Acute retinal arterial ischaemia: silent brain infarcts prevalence and short‐term recurrence. (6th September 2020) - Ayrignac, X.; Zagroun, C.; Coget, A.; Azakri, S.; Menjot de Champfleur, N.; Montcriol, A. L.; Labauge, P.; Mourand, I.; Ducros, A.; Daïen, V.; Arquizan, C.
Abstract : Background and purpose: The purpose was to evaluate, in a consecutive series of patients with isolated acute retinal ischaemia, the proportion of patients with acute silent brain infarcts (SBIs) on diffusion‐weighted imaging (DWI) and to assess risk of recurrence within 3 months. Methods: In all, 103 consecutive patients with isolated acute retinal ischaemia (central retinal artery occlusion, branch retinal artery occlusion or transient monocular vision loss) were included between January 2015 and December 2016. They all had cerebral magnetic resonance imaging including DWI as well as a standardized aetiological workup and 3 months of follow‐up. The presence of DWI‐positive cerebral lesions was recorded. Main clinical and radiological characteristics between DWI‐positive and DWI‐negative patients were compared. Results: Of the 103 patients (including 42 transient monocular vision loss), 20 (19.5%) had SBIs on DWI, which were ipsilateral to the acute retinal ischaemia in 30% and involved different and/or multiple vascular territories in 70% of cases. Ipsilateral carotid stenosis and occlusion were respectively identified in 17 and eight patients whereas cardioaortic embolism was found in 19 patients. Overall, patients with and without acute SBIs were comparable. The topography of SBIs was related to the aetiology of the acute retinal ischaemia. At 3 months of follow‐up, one patient suffered from ischaemic stroke and five had recurrent retinal ischaemia. Conclusions: Irrespective of the baseline characteristics of the patients, SBIs are present in about 20% of patients with isolated acute retinal ischaemia and may be of interest in the aetiological workup. Overall risk of recurrence is low, favoured by rapid aetiological workup and appropriate treatment.